'Give' Constructions in the Papuan Languages of Timor-Alor-Pantar - Marian Klamer; Antionette Schapper (Linguistic Discovery, 2012)
This paper describes three-participant ‘give’ constructions in ten Papuan languages of the Timor-Alor-Pantar (TAP) family. Generally lacking a class of simple ditransitive root verbs, TAP languages express ‘give’ events by means of biclausal constructions (‘take X then give Y’), serial verb constructions (‘take X give Y’), or particle-verb constructions originating in serial verb constructions. In this paper, we focus on the syntactic treatment of the gift (T), since it, unlike the other participants in ‘give’ constructions, displays considerable diversity across the TAP languages. Through the study of the synchronic variation in TAP ‘give’ constructions, we reconstruct the syntactic constructions from which the various modern constructions have developed, and sketch the grammaticalization paths that have led to them.